Systematic Review – Knowledge, Attitudes and Practices of Healthcare Workers in Reporting Adverse Drug Reactions in Sub-Saharan Africa for Pharmacovigilance - Kunene, Khontile Nobuhle; Teo, Shyh Poh (Nepal Journal of Medical Sciences, 2022)
Introduction: This study aims to assess intra and interobserver reliability of transorbital ultrasound. To review the knowledge, attitude and practices of health care workers, including doctors, nurses, pharmacists and health officers in reporting adverse drug reactions (ADRs) for pharmacovigilance in sub-Saharan Africa. Methods: PubMed, Google Scholar and Trip databases were used to identify papers relevant for the review. Search results were narrowed down through a manual review of titles and abstracts based on inclusion criteria. Results: There were 35 articles included in this review. It was found that generally, healthcare workers had inadequate knowledge regarding reporting of ADRs and pharmacovigilance. While private practice doctors have heard of pharmacovigilance and could define ADRs correctly, more than half did not know how or where to report them. The majority of healthcare workers had positive attitudes toward reporting ADRs. However, there was unwillingness in some settings due to concerns that it reflected poor clinical care on their part. All the studies identified consistently underreporting of ADRs admitted by healthcare workers. Conclusion: While HCWs have positive attitudes regarding ADR reporting, there were significant knowledge deficits, particularly regarding how to report ADRs. This contributes to the under-reporting of ADRs, which may have implications for drug safety surveillance.